Pictorial Phenomena Depicting the Family Climate of Deaf/Hard of Hearing Children and Their Hearing Families - Avrahami-Winaver, Anat; Regev, Dafna; Reiter, Shunit (Frontiers in Psychology, 2020)
This mixed method study (Explanatory Design - the Participant Selection Model) investigated the use of joint drawing (the Family Squiggle) as a family climate assessment tool for hearing families who have a deaf / hard of hearing (D/HH) child. The goal was to evaluate the possibilities of applying a quantitative approach to characterize the pictorial phenomena produced by hearing families who have a D/HH child, and then apply qualitative research approaches to better understand the meaning of these phenomena. Twenty-eight hearing families (parents and child) whose child was diagnosed as D/HH and used hearing devices (hearing aids, implant) were recruited along with 16 families with a hearing child of a similar age enrolled in a mainstream school. The sessions involved a joint drawing followed by a family interview. In the quantitative stage, pictorial phenomena for which there was a significant association between the phenomena and the group of families were defined. These were: (1) The number of dominant images, (2) Images occupying less than a quarter of the page. (3) Images with accentuated outlines. (4) Moderate colorfulness with four to five colors in each drawing. (5) Minimal representation of the face. (6) Concrete rather than creative titles. (7) Muting of conflictual themes. (8) Images reminiscent of hearing devices (hearing aids, implant). In the qualitative phase, interviews were conducted with the hearing families with a D/HH child to better understand the meaning of these pictorial phenomena. The findings suggest that each of these phenomena represent the preoccupation of the family with deafness / being hard of hearing, capture a certain aspect of family dynamics, and together provide a broader and deeper picture of the family climate and the interactions between the child's family and hearing. This assessment tool may thus be utilized when verbal tools cannot be easily applied.